Comportamento sexual de risco e prevalência das hepatites B e C, sífilis e HIV/Aids em estudantes universitários - Catão, Maria Aparecida Cavalcanti (2022)
Introduction: Sexually Transmitted Infections annually cause more than 2.3 million deaths, according to data from the World Health Organization. Viral hepatitis B and C, syphilis and HIV constitute a serious public health problem affecting vulnerable populations, in this context, young university students stand out, as they present behaviors that lead to risky sexual behavior, contributing to the incidence of these infections. Objective: To investigate the prevalence of Sexually Transmitted Infections and associated factors among university students in Paraíba. Method: Cross-sectional and analytical study, carried out with students enrolled in four campuses of the Federal University of Paraíba, from March 2021 to May 2022. Data were collected from the application of an adapted structured questionnaire, containing sociodemographic data and possible behaviors of risks for the investigated infections. To investigate the prevalence, rapid tests were used for hepatitis B and C, syphilis and HIV. The research was approved by the Research Ethics Committee of the Federal University of Paraíba, under opinion No. 4,309,767. Data analysis was performed using descriptive statistics. Results: 404 university students participated in the study. Most were female, 234 (57.9%), single, 352 (87.1%), aged between 18 and 27 years, 350 (86.6%), mean age of 23.9 years ( SD=3.96), of mixed race, 174 (43.1%), without a defined religion, 185 (45.8%), with individual monthly income < 1 minimum wage, 233 (57.7%), and monthly family income of 1 to 2 minimum wages, 161 (39.9%). The prevalence for the infections investigated was 5.0% (95%CI: 3.0-7.0). Among 404 students investigated, 12 reactive cases with reactive tests for syphilis (treponemal test) and eight for HIV were detected. No test proved to be reactive for viral hepatitis B and C. Conclusion: Communication strategies and promotion of health policies within universities linked to the prevention of these infections are necessary to strengthen health actions for this specific population.